2013
DOI: 10.1371/journal.pone.0082126
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Two Rice Varieties in Response to Rice Stripe Virus and Small Brown Planthoppers during Early Interaction

Abstract: Rice stripe, a virus disease, transmitted by a small brown planthopper (SBPH), has greatly reduced production of japonica rice in East Asia, especially in China. Although we have made great progress in mapping resistance genes, little is known about the mechanism of resistance.By de novo transcriptome assembling, we gained sufficient transcript data to analyze changes in gene expression of early interaction in response to SBPH and RSV infection in rice. Respectively 648 and 937 DEGs were detected from the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 33 publications
7
58
0
Order By: Relevance
“…6a and b). The result was similar with previous studies [38,39]. Meanwhile, the expression levels of OsWRKY were progressively increased in the early stage of infection and then decreased ( Fig.…”
Section: Comparison Of Single and Multiple Reference Gene(s) In Quantsupporting
confidence: 92%
See 1 more Smart Citation
“…6a and b). The result was similar with previous studies [38,39]. Meanwhile, the expression levels of OsWRKY were progressively increased in the early stage of infection and then decreased ( Fig.…”
Section: Comparison Of Single and Multiple Reference Gene(s) In Quantsupporting
confidence: 92%
“…To further investigate the suitability of the selected reference genes, the expression levels of two virus resistant response genes, the gene expression of OsPR1b and OsWRKY, was compared by using single and multiple reference gene(s) for normalization. In the earlier studies [38,39], for example, the expression of OsPR1b gene was strongly induced by virus infection. Our results further showed that when using TIP41-Like gene for normalization, the induction patterns of OsPR1b and OsWRKY transcripts were not stronger than those using two reference genes (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…These analyses revealed the effects of plant–virus interactions [14,21], especially about the reinforcing of the cell wall structure. Our knowledge of the mechanisms of resistance to plant pathogens was extended by RNAseq analyses of the whole transcriptomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although the transcriptional modulation of LRR-RLK genes in response to virus infection has been reported for a number of plantviral pathosystems (Naqvi et al 2011;Mandadi and Scholthof 2012;Chen et al 2013;Czosnek et al 2013;Zheng et al 2013;Andolfo et al 2014), their possible role in antiviral defense remains speculative. These genes are induced by virus infection in most cases, but repression has In this study, we focused on SlSOBIR1, a tomato LRR-RLK implicated in plant immunity and described to be a crucial interactor for RLP-mediated resistance against fungal pathogens (Liebrand et al 2013a, b).…”
Section: Discussionmentioning
confidence: 99%